2019
DOI: 10.1002/ptr.6248
|View full text |Cite
|
Sign up to set email alerts
|

Isoforskolin and forskolin attenuate lipopolysaccharide‐induced inflammation through TLR4/MyD88/NF‐κB cascades in human mononuclear leukocytes

Abstract: The principal active component of isoforskolin (ISOF) is from the plant Coleus forskohlii , native to China, which has attracted much attention for its biological effects. We hypothesize that ISOF and forskolin (FSK) pretreatment attenuates inflammation induced by lipopolysaccharide (LPS) related to toll‐like receptor 4 (TLR4), myeloid differentiation factor 88 (MyD88), and nuclear factor kappa B (NF‐κB) signaling. Mononuclear leukocytes (MLs) from healthy donors' blood samples were sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
(38 reference statements)
3
16
0
Order By: Relevance
“…Kappa B (NF-κB) in Con A-Treated Mice. NF-κB is one of the families of transcriptional factor proteins, which participates in inflammatory responses, oxidative stress, and apoptosis and regulates a variety of inflammatory factors such as IL-2, IL-6, and TNF-α [28][29][30]. The protein expression of NF-κB was further detected in ALI mice, and the result showed that intrahepatic p-p65 was markedly elevated after Con A injection.…”
Section: Effect Of Serotonin On the Activity Of Nuclear Factormentioning
confidence: 98%
See 1 more Smart Citation
“…Kappa B (NF-κB) in Con A-Treated Mice. NF-κB is one of the families of transcriptional factor proteins, which participates in inflammatory responses, oxidative stress, and apoptosis and regulates a variety of inflammatory factors such as IL-2, IL-6, and TNF-α [28][29][30]. The protein expression of NF-κB was further detected in ALI mice, and the result showed that intrahepatic p-p65 was markedly elevated after Con A injection.…”
Section: Effect Of Serotonin On the Activity Of Nuclear Factormentioning
confidence: 98%
“…Pathway in Con A-Treated Mice. As one of the earliest discovered pattern recognition receptors, TLRs are involved in inflammatory response and NF-κB activation [28,31]. Moreover, Con A stimulates the expression of TLR2, TLR4, and TLR9 and downstream pathways in liver tissue, resulting in the release of numerous proinflammatory factors [12,13].…”
Section: Effect Of Serotonin On Intrahepatic Tlr Signalingmentioning
confidence: 99%
“…cAMP then binds to the NLRP3 protein and targets it for degradation, thus interrupting the action of inflammasome and production of IL-1β in human macrophages [162]. However, forskolin may also down-regulate the protein levels of IL-1β and TNFα by influencing the TLR4/MyD88/NF-κB signal pathway [163].…”
Section: Agents Increasing Camp and Cgmpmentioning
confidence: 99%
“…In addition, they showed that pericyte stimulation with TGF-β1 and IL-1β has a synergistic release of IL-6 [40] which correlates with our finding that IL-1βis upregulated (Table 2) and a 5 fold increase in IL-6 expression ( Figure 3a). MyD88, an upstream regulator of interleukin-1 (IL-1) and tumor necrosis factor-α (TNF-α) expression [41,42] was also examined. We found expression of MyD88 was increased in the burn eschar derived-pericytes compared to normal skin derived-pericytes ( Figure 4b).…”
Section: Burn Eschar Pericytes Overexpress Inflammatory Cytokinesmentioning
confidence: 99%